Iodine-125 brachytherapy and robotic stereotactic radiotherapy — treatment options for patients with localized prostate cancer - E. A. Kiprijanov; P. A. Karnaukh; I. A. Vazhenin; E. Ya. Mozerova; A. V. Vazhenin (Вестник урологии)
Introduction. Modern radiological treatment options for patients with localized prostate cancer (PCa) have several advantages and allow achieving high rates of biochemical control.Purpose of the study. To compare immediate, proximate, and long-term results of low-dose Iodine-125 brachytherapy (I-125 BT) and robotic stereotactic radiotherapy (SBRT) in patients with localized low- and intermediate-risk PCa.Materials and methods. The study included 296 patients with localized low- and intermediate-risk PCa. I-125 BT and SBRT were performed in 208 and 88 patients, respectively. All patients with an intermediate-risk PCa were prescribed neoadjuvant androgen-deprivation therapy (NADT) with luteinizing hormone-releasing hormone analogues (LHRH) for 4-6 months. Only radiation treatment was used for low-risk PCa. As a result, two groups and four subgroups of patients were formed depending on the treatment method. The immediate, proximate, and long-term results of radiation treatment methods were studied in groups and subgroups.Results. No complications were recorded during brachytherapy I-125. Radiation cystitis grade 1 and radiation rectitis grade 1 were diagnosed after SBRT in 16.6% and 4.0% of cases, respectively. In the only I-125 BT subgroup, the PSA level during the year decreased from 8.3 to 1.1 ng/ml, in the SBRT subgroup — from 7.5 to 0.8 ng/ml. In the case of combined treatment, PSA decreased from 1.2 to 0.93 ng/ml and from 4.5 to 0.5 ng/ml, respectively. Changes in prostate volume, residual volume, and urinary quality (I-PSS) were comparable in all subgroups. Five-year cancer-specific survival and overall survival in the group of patients after SBRT was 100%, after I-125 BT — more than 90%.Conclusion. Radiation treatment options for patients with localized PCa are safe. Conducting NADT does not significantly reduce the prostate volume and does not affect the indicators of urodynamics. High rates of cancer-specific five-year survival rate testify to the effectiveness of the evaluated treatment options.